Análise estrutural e geotécnica de uma contenção de talude: estudo de caso - Abbas, Larissa Bicudo Soares [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
Urban development generates greater demand for space to build, often being necessary to change the topography of land to suit the projects designed. This work presents the slope stability analysis of an excavated for the execution of two underground floors of a residential building in the eastern part of the city of São Paulo, with cassions, grouted tieback and soil nailing to contain the horizontal loading from the massive soil. The structural design of a caisson using the Blum method and the FTool software is presented. The geotechnical analysis of global stability was performed in different stages of excavation for two sections of the containment structure according to the Simplified Bishop method through the software Slide of the Rocscience platform. The structural design resulted in a 14 meter high and 1 meter diameter caisson with reinforcement composed of 13 bars of CA50 steel of 20mm in diameter. The results obtained in the global stability analysis show that the safety of slope containment is guaranteed based on Brazilian standardization, since a safety factor was obtained within the acceptable range, that is, greater than 1.50, in both sections studied

desenvolvimento urbano gera maior demanda por espaço para construir, muitas vezes sendo necessário alterar a topografia de terrenos para que se adequem aos projetos concebidos. Este trabalho contém uma análise estrutural e geotécnica da estabilidade de um talude escavado para a execução de dois pavimentos de subsolo de um edifício residencial na zona leste da cidade de São Paulo, contando com tubulões a céu aberto, tirantes e solo grampeado para conter o carregamento horizontal proveniente do maciço de solo. Apresenta-se o dimensionamento estrutural de um tubulão a céu aberto utilizando o método de Blum e o software FTool. Já a análise geotécnica de estabilidade global foi realizada em diferentes etapas de escavação para duas seções da estrutura de contenção segundo o método de Bishop Simplificado através do software Slide da plataforma Rocscience. O dimensionamento estrutural resultou em um tubulão de 14 metros de altura e 1 metro de diâmetro com armadura composta por 13 barras de aço CA50 de 20mm de diâmetro. Os resultados obtidos na análise de estabilidade global mostram que a segurança da contenção do talude está garantida com base na normatização brasileira, com fator de segurança dentro da faixa aceitável, ou seja, maior que 1,50, em ambas as seções estudadas
Structural and geotechnical analysis of a slope containment: case study
Keywords: Análise estrutural (Engenharia); Taludes (Mecanica do solo); Geologia estrutural; Structural analysis (Engineering)